Pengaruh penggunaan smartphone terhadap kemampuan bahasa ekspresif anak usia 5-6 tahun - Kurniawati, Asih Budi; Agustina, Afifah Qonita; Syafrudin, Ulwan; Pradini, Susanthi (FKIP UNILA, 2024)
This study aims to determine the effect of smartphone use on the expressive language skills of children aged 5-6 years. This study uses a quantitative research with ex post facto methods. The sample in this study was 100 children aged 5-6 years and their parents using a cluster random sampling technique. Data collection in this study was carried out by distributing questionnaires to parents and observing children. Then, the data analysis used is a simple linear regression test. The results of the study show that there is an effect of smartphone use on children's expressive language skills. This can be seen from the calculations resaults by using simple linear regression which shows a significance level of 0.036<0.05. Based on the magnitude calculations of the influence of smartphone use, shows that it has 19.2% positive effect to the children’s expressive language skills and the other 80,8% are influenced by other factors. Support and supervision from parents along with variety of contents can make it easier for children to access various content from learning to entertainment. The most frequently visited content is watching videos through the YouTube application which can indirectly hone children's language skills.